Neuromarketing and its contribution to strengthening the image of commercial premises in Leonidas Plaza - Lemoine Quintero, Frank Ángel (2023)
Based on the actions carried out by the "Los Passaos: Emprenden con Historia" project, the objective is to perform a diagnosis of the commercial image in order to evaluate the elements that make up the brand in the businesses located in the Leónidas Plaza parish. The study focuses on a quantitative and exploratory-descriptive approach, and the sample consists of 389 businesses selected through non-probabilistic convenience sampling. Among the most representative results, it was found that the large format printing was recognized as "adequate" by 50 % of the respondents, as well as the internal signage, reflected by 31.6 % of those surveyed. However, the corporate identity of the workers was recognized as "inadequate" by 36.8 % of the total number of evaluated locations, denoting a deficiency in these three elements. The Cronbach's alpha of 0.847 recognizes a very good reliability of the instrument. It is concluded that innovation is necessary in the development of the commercial image to create better visual expectations for customers. It is recommended to continue working at the management level to achieve better projection, business focus, and visual communication at the consumer level.